THE EFFECT OF PREPARED SAMPLES OF SEQUESTRATE AGENTS AND CHELATING SURFACTANTS ON THE MODEL WASHING - Bayerová, Petra; Burgert, Ladislav; Černý, Michal; Hrdina, Radim; Vojtovič, Adam (My University, 2016)
In this work presents the results of model washing with addition of prepared samples of sequestering agents and chelating surfactants. After 20× repeated washing in hard water of 22 °dH (given in German degrees of hardness) were determined the content of ash and Ca2+ ion. The image of fabric after the model washing was evaluated by means of images from a scanning electron microscope.
Vliv připravených vzorků sekvestračních prostředků a chelatačních tenzidů na modelové praní
Keywords: sequestrate agents; chelating surfactants; washing of textile materials; sekvestrační prostředek; chelatační tenzid; praní textilních materiálů